Defining second-tier audit firms in Serbia: In search of the Small four - Stanišić, Nemanja; Mizdraković, Vule; Radojević, Tijana; Stanić, Nenad (The European Journal of Applied Economics, 2015)
In this paper, we aim to define the so-called "second tier" audit firms in the Republic of Serbia. In order to accomplish that, we have analyzed 10,555 financial statements of legal entities operating on the territory of the Republic of Serbia for the period 2010-2012. The "Big 4" audit firms have audited 1,101 of the aforementioned financial statements, whereas the rest of the statements have been audited by the remaining 38 audit firms. For the purpose of training a decision tree classification algorithm, a number of calculated financial indicators of audited entities and corresponding audit opinions issued by the "Big 4" firms have been treated as independent and dependent variables, respectively. The resulting set of rules was then applied to the rest of the sample. Based on the observed level of compliance with the "Big 4" criteria (which stands for high quality audit), we have subsequently suggested the "Small 4" audit firms in Serbia. Moreover, the results show that the "Big 4" firms and the other audit firms assign different importance to independent variables. The paper also discusses possible reasons for that and offers recommendations for future research.